The Influence of Compensation and Work Flexibility on Employee Retention with Employee Engagement as A Mediating Variable in The Millennial and Z Generations in Tangerang - Yossi Fitriani; Chandra Wibowo Widhianto (International Journal of Economics (IJEC), 2024)
This study investigates the influence of compensation and work flexibility on employee retention among Millennial and Generation Z workers in Tangerang, Indonesia, with employee engagement serving as a mediating variable. Utilizing a quantitative approach with structural equation modeling, data were collected from 152 employees through online questionnaires. The results reveal that both compensation and flexibility significantly impact employee retention, with compensation exhibiting a stronger effect. Employee engagement was found to partially mediate these relationships, amplifying the impact of both factors on retention. Notably, compensation demonstrated a more pronounced influence on both engagement and retention compared to flexibility. These findings provide crucial insights for organizations seeking to retain younger talent, emphasizing the need for competitive compensation strategies balanced with flexible work arrangements. The study contributes to the understanding of evolving workforce dynamics in emerging markets and offers practical implications for human resource management in the context of generational workplace preferences.